2012
DOI: 10.1037/spq0000012
|View full text |Cite
|
Sign up to set email alerts
|

Examining an executive function rating scale as a predictor of achievement in children at risk for behavior problems.

Abstract: Evidence suggests that executive function (EF) may be a potent and malleable predictor of academic achievement in children. Schools may be able to use this predictive power if researchers develop EF measures that not only have ecological and construct validity, but also are also efficient and affordable. To this end, Garcia-Barrera and colleagues (2011) developed a behavior rating scale from items on Behavior Assessment System for Children-Teacher Report (Reynolds & Kamphaus, 1992) to screen children for defic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 43 publications
(90 reference statements)
4
15
1
2
Order By: Relevance
“…En este contexto, resulta necesario complementar la información diagnóstica arrojada por las baterías de tests con instrumentos que puedan revelar el funcionamiento cotidiano del niño. Los inventarios de conducta alcanzan este propósito al brindar una descripción de las manifestaciones conductuales de las FE de los niños en los contextos naturales de desarrollo, como el hogar o la escuela (Anderson, Anderson, Northam, Jacobs y Mikiewiez, 2002;Frick, Barry y Kamphaus, 2010;Gioia, Isquith, Guy y Kenworthy, 2000;Sadeh, Burns y Sullivan, 2012).…”
Section: N F O R M a C I ó N D E L A R T í C U L Ounclassified
See 1 more Smart Citation
“…En este contexto, resulta necesario complementar la información diagnóstica arrojada por las baterías de tests con instrumentos que puedan revelar el funcionamiento cotidiano del niño. Los inventarios de conducta alcanzan este propósito al brindar una descripción de las manifestaciones conductuales de las FE de los niños en los contextos naturales de desarrollo, como el hogar o la escuela (Anderson, Anderson, Northam, Jacobs y Mikiewiez, 2002;Frick, Barry y Kamphaus, 2010;Gioia, Isquith, Guy y Kenworthy, 2000;Sadeh, Burns y Sullivan, 2012).…”
Section: N F O R M a C I ó N D E L A R T í C U L Ounclassified
“…Otras escalas son la Evaluación de Matson de Habilidades Sociales en Jóvenes (en inglés, Matson Evaluation of Social Skills in Youngsters -MESSY) de Matson, Rotatori y Helsel (1983), que indaga competencia social, y la Escala de Comportamiento Preescolar y Jardín de Infantes de Merrell (2003), que evalúa habilidades sociales y problemas de conducta internalizadores/externalizadores. Se han diseñado escalas comportamentales de funciones ejecutivas (Delis, 2012;Gioia, Isquith, Retzlaff y Espy, 2002;Sadeh et al, 2012); sin embargo, pocas han sido adaptadas y baremadas para población infantil latinoamericana. Un instrumento pionero en el área es el Cuestionario de Evaluación Conductual de la Función Ejecutiva -versión infantil (en inglés, Behavior Rating of Executive Function -BRIEF-P; Gioia et al, 2000) para niños preescolares (de 2 a 5 años 11 meses), que permite la evaluación de los aspectos más cotidianos, conductuales y observables de las siguientes funciones ejecutivas: inhibición, flexibilidad, control emocional, memoria de trabajo, planificación y organización.…”
Section: N F O R M a C I ó N D E L A R T í C U L Ounclassified
“…Since cognitive measures and behavioral rating scales are theorized to capture different information (Sadeh, Burns, & Sullivan, 2012; Toplak et al, 2013), we hypothesized that within each EF process the behavioral rating scales and cognitive measures of EF would both uniquely account for variance in academic performance. We expected that the cognitive measures would have qualitatively larger effect sizes than the behavioral rating measures, if only given the greater volume of empirical support for cognitive EF measures in the prediction of academic outcomes.…”
Section: The Present Studymentioning
confidence: 99%
“…One recent study found that a brief behavioral teacher rating scale in kindergarten was predictive of later behavioral and social outcomes for children, which supported the use of teacher rating scales to identify children who are at-risk early in elementary school (Racz et al 2013). Sadeh et al (2012) used a teacher rating scale of executive function to predict later outcomes, including reading ability. However, Sadeh and colleagues found that the executive function scale was not predictive of academic achievement in early elementary school after controlling for intelligence (Sadeh et al 2012).…”
Section: Understanding the Accuracy Of Teacher Ratingsmentioning
confidence: 97%
“…Sadeh et al (2012) used a teacher rating scale of executive function to predict later outcomes, including reading ability. However, Sadeh and colleagues found that the executive function scale was not predictive of academic achievement in early elementary school after controlling for intelligence (Sadeh et al 2012). Thus, more direct methods of teacher ratings for reading and early reading skills may be warranted.…”
Section: Understanding the Accuracy Of Teacher Ratingsmentioning
confidence: 99%